2012
DOI: 10.1136/gutjnl-2012-302514a.144
|View full text |Cite
|
Sign up to set email alerts
|

OC-144 The management of low-risk primary upper gastrointestinal haemorrhage in the community: a 5-year observational study

Abstract: Sung JJ, et al. Early clinical experience of the safety and effectiveness of hemospray in achieving hemostasis in patients with acute peptic ulcer bleeding. Endoscopy 2011;43:291e5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Both GBS and RS are useful to identify low‐risk cases. They could predict the necessity for endoscopic hemostasis or transfusion with a sensitivity of >95% and without any deaths when GBS <2 or RS <2 was selected as a cut‐off value; therefore, these cases could be managed on an outpatient basis . Concerning the primary treatment, a prospective study assessed the outcomes of patients with hemodynamic instability as a result of upper gastrointestinal bleeding, and compared them with historical controls.…”
Section: Initial Management Of Non‐variceal Upper Gastrointestinal Blmentioning
confidence: 99%
See 1 more Smart Citation
“…Both GBS and RS are useful to identify low‐risk cases. They could predict the necessity for endoscopic hemostasis or transfusion with a sensitivity of >95% and without any deaths when GBS <2 or RS <2 was selected as a cut‐off value; therefore, these cases could be managed on an outpatient basis . Concerning the primary treatment, a prospective study assessed the outcomes of patients with hemodynamic instability as a result of upper gastrointestinal bleeding, and compared them with historical controls.…”
Section: Initial Management Of Non‐variceal Upper Gastrointestinal Blmentioning
confidence: 99%
“…They could predict the necessity for endoscopic hemostasis or transfusion with a sensitivity of >95% and without any deaths when GBS <2 or RS <2 was selected as a cut-off value; therefore, these cases could be managed on an outpatient basis. 38,43,48,[50][51][52][53][54][55][56][57] Concerning the primary treatment, a prospective study assessed the outcomes of patients with hemodynamic instability as a result of upper gastrointestinal bleeding, and compared them with historical controls. The study revealed that patients who underwent intensive resuscitation had significantly decreased mortality and decreased interval from admission to stabilization of hemodynamics.…”
Section: Initial Management Of Non-variceal Up-per Gastrointestinal Bmentioning
confidence: 99%
“…Some studies have used those scores to identify low risk patients who might be managed as outpatients (13,14). At the other end of the spectrum, the identification of high-risk patients with an urgent need for intervention or admission to an intensive care unit (ICU), are often the main goals of the scores (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of comparison, it is possible that in less severe population, a GBS different than 0 could help to select more patients for outpatients management as in the paper by McLaughlin et al, where they chose a GBS £ 2 [17]. But as shown in this work, this criterion is probably not relevant in a severe population where only 10 patients had a GBS £ 2, including 2 patients at need or urgent UGIE.…”
Section: Discussionmentioning
confidence: 72%